KONDISI LINGKUNGAN PERAIRAN LOKASI BUDIDAYA IKAN KERAPU DI PULAU SEMUJUR, KABUPATEN BANGKA TENGAH - Imam Soehadi; Sulistiono Sulistiono; Bambang Widigdo (Fakultas Perikanan dan Ilmu Kelautan, 2021)
Aquaculture activities of grouper (Epinephenus spp) using floating cages net are mostly carried out by the community in the waters of Semujur Island, Central Bangka Regency (Bangka Belitung Islands Province). This study was conducted during February-April 2014, aims to evaluate condition of several aquatic environment parameters including water transparency, depth, current velocity, temperature, salinity, pH, and DO in the waters of Semujur Island. These parameters were given a value and weight to determine the level of feasibility. The results shows that the depth, transparency, current velocity, temperature, salinity, pH, and DO in the Semujur Island waters were 7.5-12.2 m, 2.9-5.9 m (secchi disk), 0.11-0.27 m/sec, 29.7-31.2Â°C, 31.0-32.0 %o, 7.2-7.6, 5.5-7.8 ppm, respectively. Based on these water conditions, it can be stated that the aquatic environment in the aquaculture location meets the requirements for the life of the grouper, and based on the assessment, it is classified as quite feasible-feasible.